Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fpls.2018.01584
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study of Wheat Spike Related Traits in China

Abstract: Rapid detection of allelic variation and identification of advantage haplotypes responsible for spike related traits play a crucial role in wheat yield improvement. The released genome sequence of hexaploid wheat (Chinese Spring) provides an extraordinary opportunity for rapid detection of natural variation and promotes breeding application. Here, selection signals detection and genome-wide association study (GWAS) were conducted for spike related traits. Based on the genotyping results by 90K SNP chip, 192 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 83 publications
(98 reference statements)
12
54
1
Order By: Relevance
“…In other words, SlPS, TKW and SlC were more stable than FTN and KPSl. Consistent with many other reports, FTN had a low heritability and was strongly influenced by environments [5,9,31] and KPSl also displayed relatively low heritability, whereas SlPS, TKW and SlC had relatively higher heritabilities [3,9,[32][33][34].…”
Section: Yield-related Traits Slps Tkw and Slc Exhibited Relativelysupporting
confidence: 90%
“…In other words, SlPS, TKW and SlC were more stable than FTN and KPSl. Consistent with many other reports, FTN had a low heritability and was strongly influenced by environments [5,9,31] and KPSl also displayed relatively low heritability, whereas SlPS, TKW and SlC had relatively higher heritabilities [3,9,[32][33][34].…”
Section: Yield-related Traits Slps Tkw and Slc Exhibited Relativelysupporting
confidence: 90%
“…The positive relationships between FSS (or FSS%), GNFS with BY, TKW, HI, SPS and GN that found in the current study, indicate that improving grain yield through enhancing spikelet fertility together with TKW, SPS and BY is plausible. It might be attributed to the genetic material (ancient cultivars) used in the current study which are carrying allele(s) that not present, or present at low frequency in breeding lines or elite/modern cultivars used in the previous studies 8, 24,25 . The elite/ modern cultivars were selected for a specific purpose based on origin 8 , and always characterized with low number of kernels per spikelet, and less resistance/tolerance to biotic/abiotic stresses compared with old cultivars 26 .…”
Section: Discussionmentioning
confidence: 96%
“…The newly added spikelet related-traits in this study demonstrated the importance of studying such traits which showed high natural variation. The natural variation of spikelet fertility/sterility traits and grain-yield-related traits has been recently explored in wheat 8,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent past, several genes controlling spike morphology have been investigated and described in temperate cereals (Gauley and Boden 2019; Koppolu and Schnurbusch 2019). From a plant breederā€™s viewpoint, most spike morphological traits in wheat such as spike length and spikelet number behave as quantitative traits, and various QTL and association studies have recently been published (Deng et al 2017; Guo et al 2017; Liu et al 2018; Sakuma et al 2019; WĆ¼rschum et al 2018; Zhai et al 2016). High associations and prediction abilities for total and fertile spikelet number as well as spike length and grain yield were also reported (Guo et al 2018).…”
Section: Introductionmentioning
confidence: 99%